Energy intensity, supply chain digitization, technological progress bias in China's industrial sectors - Işık, Cem; Yan, Jiale; Ongan, Serdar (Energy economics, 2025)
Supply chain digitization through the development of digital technologies provides an opportunity to promote innovation and technological advancement in enterprises. This study first adopts the supply-side economics (Lucas, 1990) approach to measure the bias of Technological Progress (TP) in China's industrial sectors and analyzes the specific mechanisms. Based on the three-factor nested CES production function of energy, capital, and labor, this study further examines the energy intensity effect of TP bias due to supply chain digitization for 36 Chinese industrial sectors from 2008 to 2021. The findings are as follows. First, supply chain digitization-induced TP bias significantly mitigates the energy intensity of industrial sectors through the relative share of energy factors. Second, there are differences in the impact on energy intensity across sectors with different levels of competition and supply chain concentration. Third, supply chain digitization induced TP bias toward capital, which is the main reason for the decrease in the relative share of energy factors. Therefore, policymakers should consider sectoral characteristics and the effects of digitalization when designing their energy policies and technology investments. They should also stimulate economic growth by optimizing capital and energy use by developing digital technologies. [Display omitted] •Construct constant elasticity of substitution production function with energy component•First test of the bias of technological progress due to the supply chain digitalization•Supply chain digitization reduces energy intensity through capital technology progress.